Climate change, cultural continuity and ecological grief: Insights from the Sámi Homeland - Markkula, Inkeri; Turunen, Minna; Rikkonen, Taru; Rasmus, Sirpa; Koski, Veina; Welker, Jeffrey M. (Springer Nature, 2024)
Arctic regions are warming significantly faster than other parts of the globe, leading to changes in snow, ice and weather conditions, ecosystems and local cultures. These changes have brought worry and concern and triggered feelings of loss among Arctic Indigenous Peoples and local communities. Recently, research has started to address emotional and social dimensions of climate change, framed through the concept of ecological grief. In this study, we examine sociocultural impacts of climate change and expressions of ecological grief among members of reindeer herding communities in the Sámi Homeland in Finland. Results indicate that ecological grief is felt in connection to major environmental concerns in the area: changes in winter weather and extreme weather events, Atlantic salmon decline and land use changes, which all have cultural and social consequences. Our results indicate that ecological grief is strongly associated with ecological losses, but also with political decisions regarding natural resource governance.
Keywords: Atlantic salmon; climate change; ecological grief; environmental change; reindeer herding; Sámi Homeland